Оценка полноты статистической информации о развитии делового туризма в АРК - Максимюк, М.Н. (Культура народов Причерноморья, 2013)
В процессе исследования изучена полнота официальных источников информации о
развитии делового туризма в АРК и Украине; выявлены недостатки в отечественных официальных
источниках информации о развитии делового туризма. Предложено уточнить определение туризма в
ЗУ «О туризме» в соответствии с рекомендациями ООН; совершенствовать сбор и обобщение
статистической информации о развитии туризма и делового туризма в частности согласно
Международным рекомендациям по статистике туризма (2008 г.) и Вспомогательного счета туризма:
рекомендуемой методологической основы (2008 г.), подготовленные ООН. У процесі дослідження вивчена повнота офіційних джерел інформації про розвиток ділового
туризму в АРК і Україні; виявлені недоліки у вітчизняних офіційних джерелах інформації про розвиток
ділового туризму. Запропоновано уточнити визначення туризму в ЗУ «Про туризм» відповідно до
рекомендацій ООН; удосконалювати збір і узагальнення статистичної інформації про розвиток
туризму й ділового туризму зокрема згідно з Міжнародними рекомендаціями по статистиці туризму
(2008 р.) і Допоміжного рахунку туризму: рекомендованої методологічної основи (2008 р.), які
підготовлені ООН. During the research of the completeness of statistical information official sources on the business
tourism development in Crimea and Ukraine was studied: Statistics administration in Crimea, State Statistics
Service of Ukraine and World Travel & Tourism Council (WTTC); disadvantages in domestic official sources of
statistical information on the business tourism development were found out: information presented only about
the amount of tourists, but not about the business tourist expenses.
For the improvement of quality of statistical information on the business tourism development in Crimea and
Ukraine it is necessary to: develop and adopt the way of completion of new government statistical observation
form №1-tourism (annual) “Travel activity report over 20__ year”; to specify the definition of tourism in the
Law of Ukraine “About tourism” according to United Nations recommendations; to perfect the collection and
generalization of statistical information on development of tourism and the business tourism in particular
according to International Recommendations for Tourism Statistics 2008 and Tourism Satellite Account:
Recommended Methodological Framework, prepared by the Statistics Division of the United Nations
Department of Economic and Social Affairs (UN DESA).
This will enable tourism statistics data to take part in GDP of Ukraine formation (to estimate tourism
contribution to GDP) and to conduct the comparative analysis and interstate comparisons between tourism
statistics.